Genetic variant in TNF-Alpha gene and its plasma level in relation to obstructive sleep apnoea in the Pakistani population - admin,; Ambreen Qamar,; Muhammad Hanif,; Zeba Haque,; Sitwat Zehra,; Saifullah Baig,; Abdul Samad, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the link between tumour necrosis factor-alpha -308 guanine/adenine polymorphism and tumour necrosis factor-alpha plasma levels in relation to obstructive sleep apnoea. Method: The cross-sectional study was conducted from December 2018 to March 2021 at the sleep clinic of Dow University Hospital, Karachi, on obstructive sleep apnoea patients and healthy controls. Epworth Sleep Scale score was used to determine daytime sleepiness, while full-night polysomnography was carried out for obstructive sleep apnoea confirmation and categorisation according to severity. Blood sample collection was followed by deoxyribonucleic acid extraction and plasma tumour necrosis factor-alpha measurement using enzyme-linked immunosorbent assay. Genotype distribution and allelic frequency were assessed. Data was analysed using SPSS 20. Results: Out of the 225 subjects, with a mean age of 47.68±9.88 years, 132 (58.7%) were males, and 93 (41.3%) were females. Among them, 150 (66.7%) were patients, and 75 (33.3%) were controls. Heterozygous tumour necrosis factor-alpha -308 guanine/adenine genotypes were significantly higher among the patients (p<0.05). Minor allele - 308 adenine showed an association with obstructive sleep apnoea, its severity, higher tumour necrosis factor-alpha levels, neck circumference, excessive daytime sleepiness and the presence of hypertension (p<0.05). Conclusion: Tumour necrosis factor-alpha -308 adenine allele and higher tumour necrosis factor-alpha levels were found to be linked with obstructive sleep apnoea. The polymorphism also showed an association with hypertension in obstructive sleep apnoea patients. Key Words: Tumour necrosis, polysomnography, alleles, sleep apnea, obstructive, hypert